Sociolinguistic consequences of language contact between multilingual communities in Sarawak, East Malaysia, Borneo - Norahim, Norazuna (2nd Westminister Linguistics Conference Language-Contact-Change-Maintenance-and-Loss, 2011)
This paper discusses language contact situations in multilingual communities in the south-western part of Sarawak, with examples drawn from two case studies: (i) contact between two major ethnic communities, Iban and Malay, in a “rural” setting, and (ii) language contact situation in an urban setting with reference to the Bidayuh, a minority community. In these communities, speakers employ several languages at their disposal in a given situation. Choice at the micro-level is largely dictated by the types of interlocutors, and speaker’s social network. In view of that, the existence of bilingualism/multilingualism among speakers does not necessarily reflect language shift in progress. The paper provides an alternative research framework to capture language choice patterns in such multilingual communities. The framework uses “speaker variation in language choice” and the “implicational scaling” technique in analysis. By means of such construct, it was possible to describe changes in language choice patterns of community members, and to show speaker variables rather than social variables (e.g. age, gender) as major variables in description of the process of language shift and maintenance. It was also possible to identify the social profiles of speakers that are initiating changes in language choice patterns in these communities.